Pemberian Insentif Terhadap Turnover Intention Pada Perusahaan Properti - Mocino; Kurnianing Isulolipu; Antonius Widi Hardianto (Administratio, 2024)
Human resources are the driving force of a company that determines performance in achieving company goals. Each employee certainly has a different performance from one employee to another, for example within one month salesperson A can reach the target, while salesperson B does not reach the target. Companies can stimulate employee performance through the provision of incentives which are interpreted as a form of appreciation for achieving a target or exceeding it. Incentive programs need to be designed in an attractive way to generate, increase, and maintain work motivation, so that performance meets targets. If the incentive program is deemed unattractive, employees may feel unappreciated and bored with the work situation, resulting in a desire to leave the company (turnover intention). This research was conducted at a property company located in Jakarta, PT. X has a sales force of 35 people and all of them are used as research respondents. The purpose of this study was to analyze the effect of providing incentives on the level of turnover intention of PT. X with descriptive analysis techniques, normality test, linearity test, simple linear regression test, coefficient of determination test, correlation test, and t test. The results showed that the incentive variable had a significant negative effect on the turnover intention variable by 11.9%.